Forging interdisciplinary collaborations : comprehensive mental health programming across P-16 education systems - Levy, Ian P.; Steen, Sammy (Emerald Publishing Limited, 2025)
Education professionals have consistently recognized the profound impact of mental health on students' learning and academic achievement. Numerous studies document how mental health influences PreK-16 outcomes, including graduation rates, academic performance, coursework completion, motivation, and emotional stability. These challenges are further complicated by the demands placed on the PreK-16 staff responsible for supporting student mental health. Often, these staff members themselves are at risk of experiencing high levels of stress and burnout due to the emotional and psychological toll of their roles. Forging Interdisciplinary Collaborations explores a wide range of mental health issues affecting PreK-16 schools and highlights both successful and unsuccessful approaches taken by school districts, colleges, and universities to promote the emotional well-being of students and staff. Through a collection of chapters written by interdisciplinary professionals in education, the volume seeks to break down the silos within the field of education and foster collaboration on addressing student mental health through both preventative and responsive approaches. Each chapter offers practical recommendations for mental health practitioners, teachers, higher education faculty, parents, and students, providing concrete strategies to support mental health across all educational settings.
Includes index.
Keywords: Teachers -- Mental health.; Students -- Mental health.; Education -- Schools -- Levels -- General.; Educational psychology.; Schools and pre-schools.; elektronické knihy; electronic books